The transcription factor Rap1p is required for tolerance to cell‐wall perturbing agents and for cell‐wall maintenance in Saccharomyces cerevisiae. Issue 1 (3rd December 2014) - Azad, Gajendra Kumar; Singh, Vikash; Baranwal, Shivani; Thakare, Mayur Jankiram; Tomar, Raghuvir S.
Abstract : Yeast repressor activator protein (Rap1p) is involved in genomic stability and transcriptional regulation. We explored the function of Rap1p in yeast physiology using Rap1p truncation mutants. Our results revealed that the N‐terminal truncation of Rap1p (Rap1ΔN) leads to hypersensitivity towards elevated temperature and cell‐wall perturbing agents. Cell wall analysis showed an increase in the chitin and glucan content in Rap1ΔN cells as compared with wild type cells. Accordingly, mutant cells had a twofold thicker cell wall, as observed by electron microscopy. Furthermore, Rap1ΔN cells had increased levels of phosphorylated Slt2p, a MAP kinase of the cell wall integrity pathway. Mutant cells also had elevated levels of cell wall integrity response transcripts. Taken together, our findings suggest a connection between Rap1p and cell wall homeostasis. Abstract : Rap1p provides tolerance to heat and cell wall perturbing agents. Removal of N terminal domain of Rap1 (Rap1ΔN) causes cell aggregation phenotype. Rap1ΔN cells exhibits increase in thickness of cell wall. Slt2p remains activated in Rap1ΔN mutant. Rap1ΔN shows increase in expression of cell wall damage response genes.